(untitled) - Messadié, Gérald. (New York, 1991)
Throughout the nineteenth century, inventors produced simple electric lights. For example, Joseph Swan produced a simple electric light, but, he struggled to maintain a power source and the filament soon burned out when the vacuum was exhausted. It was Thomas Edison who made the lightbulb into a practical low current version. He used a filament based on a burned sewing thread.
Keywords: Phát minh,Inventions; Sáng chế,History